Understanding Chemical Reactions of Cellulose at High Temperatures and Employing Pretreatments for Carbon Fiber Production - Kim, Sung-Soo (제132회 대한화학회 학술발표회 총회 및 기기전시회, 2023)
Polyacylonitrile PANbased fibers have been widely used as a precursor for the fabrication of highperformance carbon fibers CFs which can be applied in aerospace sporting goods and automobile industries due to their superior specific strength However one of the most pr ominent issues related to PANbased CFs is their high fabrication cost As more than half of the total cost of manufacturing PANbased CF is represented by the PAN precursor other polymeric materials have been investigated and utilized as an alternative precursor to fabricate cos teffective CFs Cellulose which consists of linear chains of β14linked dglucose units has been considered as biorenewable and lowcost precursors for the production of CFs Various natural cellulose fibers have been extensively utilized as a source of textile fibers throughout h uman history However one major issue associated with the cellulose pyrolysis arises from side reactions that release volatile substances l eading to a low char yield after carbonization and poor mechanical properties of the resulting CFs In this work we demonstrate that both p retreatments with sulfuric acid and electron beam irradiation can significantly increase the char yield for the fabrication of cellulosederived CFs Our experimental results and previous studies on the mechanism of cellulose pyrolysis mutually indicate that sulfuric acid and electron beam effectively induced the fragmentation of cellulose chains which plays a significant role in augmenting the char yield after subsequent carbonization as well as reducing the time for thermostabilization by a factor of 10 The resulting CFs exhibited measurable mechanical pro perties in stark contrast to the inherently brittle CFs generated without these pretreatments.